The queer girl is going to be okay - Walls, Dale (Levine Querido, 2023)
"Queer Love. Something Dawn wants, desperately, but does not have. But maybe, if she can capture it, film it, interview the people who have it, queer love will be hers someday. Or, at least, she'll have made a documentary about it. A documentary that, hopefully, will win Dawn a scholarship to film school. Many obstacles stand in the way of completing her film, but her best friends Edie and Georgia are there to help her reach her goal, no matter what it takes. A touching and joyous story of queer friendship and girlhood set in the vibrant city of Houston, THE QUEER GIRL IS GOING TO BE OKAY will make you laugh, make you cry, and make you believe that eventually, everything will be okay" --